Allan Sekula, du charbon à la mer : matérialisme culturel et réalisme critique - Florent Le Demazel (Images du Travail, Travail des Images)
Gone in 2013, Allan Sekula is a theorist and a photographer, with a strong and political work. Under the influence of Walter Benjamin, he wanted to write an history of photography in a materialist perspective. He defends the idea that the sense of a picture depends on the discursive and social context, not in the picture itself. Such a history emphasizes relations of production and conflicts of interest in labor’s representations. Sekula’s essay, Photography, Between Labor and Capital (1983), returns to the evolutions of photography and industrial capitalism, with a focus on the pictures of coal mine. With a keen awareness of strength and weakness of his medium, Sekula used a fragmentary aesthetic: workers’ bodies are divided by the modern management; the globalisation scattered in strategic and unequal spaces around the world. And by the addition of text in order to reveal a possible ideological domination, or the exchanges between the artist and his subject, his own work shows at last a fragmented reality. Often invisible, these relations are essential in the process of making pictures.